Diversification vs. specialization as alternative strategies for economic development : can we settle a debate by looking at the empirical evidence? - Kaulich, Florian (UNIDO ViennaAT, 2012)
Contributes new empirical findings to the recent discussion on the stages of economic diversification and specialisation. Outlines the different strands of discussion on diversification and specialisation. Explains briefly the statistical methods and datasets used in the subsequent econometric analysis. Presents the empirical results of this analysis in detail.